2021
DOI: 10.1097/mpg.0000000000003041
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Biopsy Technique for the Diagnosis of Hirschsprung Disease in Children

Abstract: The diagnosis of Hirschsprung disease (HD) depends on the histopathological analysis of rectal biopsies. This review aims to define the best rectal biopsy technique. A systematic literature review and proportional meta-analysis of the available case series studies of rectal biopsies were performed in this study. All case series with more than five rectal biopsies in children younger than 18 years of age suspected of HD that described at least one type of rectal biopsy were included. The studies that did not sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The first aim of our study was to identify the prevalence and severity of complications following RSB. In accordance with two systematic reviews, 15,16 we found a low prevalence of complications following RSB. However, our findings contrast with those of a systematic review by Friedmacher and Puri, which included a total of 14,053 RSBs, in 58 cohorts, obtained at a median age of 14.4 months.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The first aim of our study was to identify the prevalence and severity of complications following RSB. In accordance with two systematic reviews, 15,16 we found a low prevalence of complications following RSB. However, our findings contrast with those of a systematic review by Friedmacher and Puri, which included a total of 14,053 RSBs, in 58 cohorts, obtained at a median age of 14.4 months.…”
Section: Discussionsupporting
confidence: 90%
“…One possibility is that different biopsy suction instruments were used in the studies covered in the review compared with our study. 15,16 However, the types of instruments have not been reported by Friedmacher and Puri and therefore this comparison cannot be made. 15 Based on our data, we suggest a low threshold for obtaining RSBs in young children presenting with symptoms suggestive of HD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may necessitate larger biopsies in older children to achieve an equivalent adequate result. [9] [10] [11] In the present study we demonstrated that taking more than one biopsy (multiple passes) during a suction rectal biopsy procedure also greatly decreased the chances of an inadequate biopsy. The addition of calretinin staining as a means of reducing inadequacy rates is also important to note, as none of the suction biopsies where calretinin staining was performed were inadequate compared to 14% of those without calretinin staining.…”
Section: Rectal Suction Biopsy Vs Incisional Biopsymentioning
confidence: 82%
“…However, the rate of inadequate suction rectal biopsy has been demonstrated to be signi cant with a recent systematic review of the literature estimating 12% diagnostic insu ciency associated with suction biopsy. [9] Practice at our institution has generally been to perform suction rectal biopsy in infants and younger children, and incisional biopsy on older children based on the potential likelihood of increased inadequacy rate associated with suction biopsy with older age patients. [10] [11] Currently, no universal standard or protocol exists for age at which suction vs incisional biopsy should be performed and the literature is variable.…”
Section: Introductionmentioning
confidence: 99%